Temporomandibular Joint Disorders and Orthodontics - A Review of Literature - Mishra, Sumeet; Manerikar, Ravindra; Sonawane, Aishwarya; Viragi, Prashant; Toshniwal, N G (Annals of the Romanian society for cell biology, 2020)
Prevalence studies show the occurrence of temporomandibular disorders in young adult and teenaged of which 30% of the population undergo orthodontic treatment during this phase. [...]there have been conflicting opinions if the orthodontic treatment causes any form of temporomandibular dysfunction; or treating the temporomandibular dysfunction via orthodontic treatments. Temporomandibular disorders (TMD) are a collection of dental and medical conditions affecting TMJ and / or associated structures such as skeletal muscle, and the tissues of the affected tissues. Since all the muscles related with manducate can be affected by the disease, the pain is often felt away from the limb, hence the name Craniomandibular Disorder. 1 The symptoms of the disorder may affect the quality of an individual's life and have a psychogenic impact on an individual. Other etiologic factors such as multicausal include genetic, developmental, physiologic, traumatic, pathologic, environmental and behavioral factors are considered more important.5 Occlusion and TMD McNamara, Seligman and Okeson has written 8 contradictory inferences the importance of occlusion as an etiologic factor: -6,7 1) Signs and symptoms of TMD occur in healthy people. 2) The signs and symptoms of TMD increase with age, especially during teen age. [...]TMD arising between dental treatment may not be related to orthodontic treatment. 3) Orthodontic treatment around puberty does not increase or decrease the risk of developing TMD later in life. 4) Tooth Removal as part of the dental treatment program does not increase the risk of developing TMD. 5) No higher risk of TMD is associated with any type of orthodontic equipment. 6) Although stable prevention is the goal of rational orthodontic treatment, failure to achieve proper gnathological closure does not cause the signs and symptoms of TMD. 7) There is no way to prevent TMD shown. 8) where severe signs and symptoms of TMD are present, simple treatment may reduce them in most patients. No statistical link was noted between the history of previous dental treatment and the internal confusion of TMJ.9 Orthodontic extractions and TMD In studies regarding the association of TMD and orthodontic extractions an evaluation of 29 orthodontically treated patients with maxillary and mandibular premolar extractions showed no significant differences in TMD signs and the symptoms.10 In a study conducted by Artun J et al, in 29 woman patients treated with Class II, Division 1 malocclusion it was considered that the condylar position was far behind the right medial and medial segments in patients treated with the removal of maxillary first premolar.11 In a study involving 65 females, it was inferred that the orthodontic correction with or without tooth removal did not grow the risk for TMD or aggravate pretreatment indication of TMD.12 Malocclusion, without treatment,and TMD According to studies conducted by Helm, which included a twenty year follow-up using questionnaires to self-report symptoms and signs showed that while most aspects of malocclusion were consistent with patients with TMD there was no strong correlation between them and thus malocclusion tests, on the basis of recognise those at risk of TMD, were inappropriate.13 Orthodontic treatment and improvement in the signs of symptoms of TMD A previous study by Henrikson, which examined young girls being treated, showed that in the treatment group there was a significant reduction in the severity of symptoms after treatment, but that click, a common symptom of TMD, increased both treated, untreated and common groups within 2 years of monitoring.14,15 Orthodontic treatment and the development of TMD Peltola investigated the hypothesis that radiographic condylar findings in treated patients are associated with clinical TMD.